The Potential For Ecotourism In The Coastal Mangrove Ecosystem Of Panrita Lopi In The Village Tanjung Limau Sub-Dstrict Muara Badak - Muhammad Yasser; Nurul Hikma; Widya Kusumaningrum; Omega Raya Simarangkir (Berkala Perikanan Terubuk, 2022)
This research was conducted in April to August 2019 to determine the potential of Mangrove Ecotourism in the village Tanjung Limau, Muara Badak. The result of the suitability analysis show that the mangrove area of the Pangempang area is included in the appropriate or standard category (S2) namely 62%, which is suitable for development into ecotourism because it has a good density value and various type of mangrove and the presence of various types of biota such as birds, crabs, mollusca, fish and monkeys. Based on the type of mangrove shows that station I there are 7 type namely Brugeria gymnorhiza, Avicennia rumphiana, Avicennia officinalis, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa and Avicennia marina. Station II namely Brugeria gymnorhiza, Avicennia rumphiana, Avicennia officinalis, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa and Avicennia marina. Station III namely Brugeria gymnorhiza, Avicennia rumphiana, Avicennia officinalis, Rhizophora apiculata and Avicennia marina.